Efficacies of Entecavir against Lamivudine-Resistant Hepatitis B Virus Replication and Recombinant Polymerases In Vitro - Levine, S. (American Society for Microbiology, 2002)
Entecavir (ETV) is a potent and selective inhibitor of hepatitis B virus (HBV) replication in vitro and in vivo that is currently in clinical trials for the treatment of chronic HBV infections. A major limitation of the current HBV antiviral therapy, lamivudine (3TC), is the emergence of drug-resistant HBV in a majority of treated patients due to specific mutations in the nucleotide binding site of HBV DNA polymerase (HBV Pol). To determine the effects of 3TC resistance mutations on inhibition by ETV triphosphate (ETV-TP), a series of in vitro studies were performed. The inhibition of wild-type and 3TC-resistant HBV Pol by ETV-TP was measured using recombinant HBV nucleocapsids, and compared to that of 3TC-TP. These enzyme inhibition studies demonstrated that ETV-TP is a highly potent inhibitor of wild-type HBV Pol and is 100- to 300-fold more potent than 3TC-TP against 3TC-resistant HBV Pol. Cell culture assays were used to gauge the potential for antiviral cross-resistance of 3TC-resistant mutants to ETV. Results demonstrated that ETV inhibited the replication of 3TC-resistant HBV, but 20- to 30-fold higher concentrations were required. To gain further perspective regarding the potential therapeutic use of ETV, its phosphorylation was examined in hepatoma cells treated with extracellular concentrations representative of drug levels in plasma in ETV-treated patients. At these concentrations, intracellular ETV-TP accumulated to levels expected to inhibit the enzyme activity of both wild-type and 3TC-resistant HBV Pol. These findings are predictive of potent antiviral activity of ETV against both wild-type and 3TC-resistant HBV.